Into the arms of strangers stories of the Kindertransport - Harris, Mark Jonathan 1941- (Bloomsbury, 2000)
Chronicles the events and people involved in the rescue of 10,000 children from Nazi territories, and what happened after the war. Official tie-in to the Warner Brothers documentary. First hand account of the extraordinary rescue mission of 10,000 children before the outbreak of World War II. For nine months before the outbreak of World War II, Britain conducted an extraordinary rescue mission. It opened its doors to over 10,000 endangered children, 90 percent of them Jewish, from Germany, Austria, and Czechoslovakia. These children were taken into foster homes and hostels in Britain, expecting eventually to be reunited with their parents. Most of the children never saw their families again. Into the Arms of Strangers recounts the remarkable story of this rescue operation, known as the Kindertransport, and its dramatic impact on the lives of the children who were saved. The book is the companion to the feature-length documentary which was released in the theatres by Warner Bros. in Fall 2000. It contains stories in their own words from the child survivors, rescuers, parents, and foster parents. They recount, in harrowing detail, the effects of the Nazi's reign of terror, the horror of Kristallnacht, the agonizing decision by the parents to send their children away, the journey, the difficulties of adjustment in Britain, the outbreak of war, and the children's tragic discovery afterward that most of their parents had perished in concentration camps. The stories are heartbreaking, but also inspiring. These are the stories of those who survived with the help of others; they are stories about the strength and resolve of children; and most astonishing, these are stories not yet heard about the Holocaust.
Keywords: Geschichte 1939-1945; Geschichte 1938-1945; Geschichte; Juden; Jewish children -- Germany -- Biography; Jewish children -- Great Britain -- Biography; Jewish refugees -- Great Britain -- Biography; Jews -- Germany -- Biography; Jews -- Germany -- History -- 1933-1945; Refugees -- Great Britain -- Biography; Kindertransport; Drittes Reich; Exil; Kind; Deutschland; Großbritannien; Biografie; Erlebnisbericht